Harvesting of Autogenous Bone Graft from the Ascending Mandibular Ramus Compared with the Chin Region: a Systematic Review and Meta-Analysis Focusing on Complications and Donor Site Morbidity - Thomas Starch-Jensen; Daniel Deluiz; Sagar Deb; Niels Henrik Bruun; Eduardo Muniz Barretto Tinoco (Stilus Optimus, 2020)
Objectives: The aim of this systematic review was to test the hypothesis of no difference in complications and donor site morbidity following harvesting of autogenous bone graft from the ascending mandibular ramus compared with the chin region. Material and Methods: MEDLINE (PubMed), Embase and Cochrane Library search in combination with a hand-search of relevant journals was conducted including human studies published in English through June 26, 2020. Randomized and controlled trials were included. Outcome measures included pain, infection, mucosal dehiscence, altered sensation or vitality of adjacent tooth/teeth, neurosensory disturbances and patient-reported outcome measures. Risk of bias was assessed by Cochrane risk of bias tool and Newcastle-Ottawa Scale. Results: Ten controlled trials of high-quality fulfilled inclusion criteria. Risk of infection and mucosal dehiscence seems to be comparable with the two treatment modalities. However, harvesting from the chin seems to be associated with increased risk of pain, altered sensation or loss of tooth vitality, and neurosensory disturbances. Willingness to undergo the same treatment again was reported with both treatment modalities, but significant higher satisfaction, lower discomfort and acceptance of the surgical procedure was reported following harvesting from the ascending mandibular ramus. Conclusions: The hypothesis was rejected due to higher prevalence and severity of complications and donor site morbidity following harvesting of autogenous bone graft from the chin region. Dissimilar evaluation methods and various methodological confounding factors posed serious restrictions for literature review in a quantitative systematic manner. Conclusions drawn from results of this systematic review should therefore be interpreted with caution.